Understanding test-takers' perceptions of difficulty in EAP vocabulary tests: The role of experiential factors. (July 2017) - Oruç Ertürk, Nesrin; Mumford, Simon E.
This study, conducted by two researchers who were also multiple-choice question (MCQ) test item writers at a private English-medium university in an English as a foreign language (EFL) context, was designed to shed light on the factors that influence test-takers' perceptions of difficulty in English for academic purposes (EAP) vocabulary, with the aim of improving test writers' judgments on difficulty. The research consisted of a survey of 588 test-takers, followed by a focus group interview, aimed at investigating the relative influences of test-taker factors and word factors on difficulty perceptions. Results reveal a complex interaction of factors influencing perceived difficulty dominated by the educational, and particularly, the social context. Factors traditionally associated with vocabulary difficulty, such as abstractness and word length, appeared to have little influence. The researchers concluded that rather than basing their intuitions regarding vocabulary difficulty on language-lesson input or surface features of words, EAP vocabulary test writers need a clear understanding of test-takers' difficulty perceptions, and how these emerge from interactions between academic, social and linguistic factors. As a basis for EAP vocabulary item writer training, four main implications are drawn, related to test-takers' social and educational background, field of study, the features of academic words, and the test itself.